2015
DOI: 10.1007/s11947-015-1494-z
|View full text |Cite
|
Sign up to set email alerts
|

Jet Milling Effect on Functionality, Quality and In Vitro Digestibility of Whole Wheat Flour and Bread

Abstract: 9Jet milling is an ultragrinding process in order to produce superfine powders with 10 increased functionalities. The effect of milling pressure, feed rate, vibration rate of 11 feeder and feedback of jet milling on whole wheat flour functionality and the potential 12 of those flours for breadmaking with the goal of improving bread quality and 13 digestibility was investigated. Increasing milling pressure (from 4 to 8 bar), 14 decreasing feed rate (from 0.67 to 5.18 kg/h) and/or using recirculation augmented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 29 publications
(28 reference statements)
8
30
3
1
Order By: Relevance
“…These C microparticles were embedded inside larger clusters greater than 100 μm in general and they seem to be randomly distributed throughout the flour sample. The size and shape of the wheat flour are consistent with those obtained by ultragrinding methods such as the jet milling method . At the end of 15 min and 100 min of the ultrasonication process, U15 and U100 were formed.…”
Section: Resultssupporting
confidence: 78%
“…These C microparticles were embedded inside larger clusters greater than 100 μm in general and they seem to be randomly distributed throughout the flour sample. The size and shape of the wheat flour are consistent with those obtained by ultragrinding methods such as the jet milling method . At the end of 15 min and 100 min of the ultrasonication process, U15 and U100 were formed.…”
Section: Resultssupporting
confidence: 78%
“…Moisture content decreased as the particle size diminished, because higher surface area was available to interact. Moreover, jet milling reduces moisture content of flours due to their exposure to dry air of high flow rate as has been already observed (Protonotariou et al 2015). Concerning damaged starch, it increased owing to milling (Table 2).…”
Section: Chemical Compositionmentioning
confidence: 54%
“…It has been reported that finer fractions had lower ash and higher dry gluten than coarser fractions when wheat flour was fractioned by sieving (Sakhare et al 2014). Nevertheless, Protonotariou et al (2015) do not observed any trend when studying the impact of jet milling intensity on the protein and ash content of whole wheat flour.…”
Section: Chemical Compositionmentioning
confidence: 69%
See 1 more Smart Citation
“…Jet‐milling of wheat flour increased its water holding capacity (WHC) and lightened its color (Protonotariou and others ). Jet‐milled flour produced texturally harder bread with lower volume, luminosity, moisture, and glycemic index compared to the un‐milled control (Protonotariou and others ). Superfine soy flour had higher WHC, solubility, swelling, fat binding, and sensory scores compared with the control (Muttakin and others ).…”
Section: Introductionmentioning
confidence: 90%